Limit Distribution for The Weighted Rank Correlation Coefficient, rw - Joaquim F. Pinto da Costa; Luís A.C. Roque (Revstat Statistical Journal, 2006)
A weighted rank correlation coefficient, inspired by Spearman’s rank correlation coefficient, has been proposed recently by Pinto da Costa & Soares [5]. Unlike Spearman’s coefficient, which treats all ranks equally, rW weights the distance between two ranks using a linear function of those ranks, giving more importance to top ranks than lower ones. In this work we prove that rW has a gaussian limit distribution, using the methodology employed in [7].